2016
DOI: 10.1016/j.ejps.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Nanovesicular liposome-encapsulated hemoglobin (LEH) prevents multi-organ injuries in a rat model of hemorrhagic shock

Abstract: The goals of resuscitation in hemorrhagic shock are to correct oxygen deficit and to maintain perfusion pressure to the vital organs. We created liposome-encapsulated hemoglobin (LEH) as a nanoparticulate oxygen carrier (216 ± 2 nm) containing 7.2 g/dL hemoglobin, and examined its ability to prevent the systemic manifestations of hemorrhagic shock (45% blood loss) in a rat model. We collected plasma after 6 h of shock and LEH resuscitation, and determined the circulating biomarkers of systemic inflammation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Further research is currently being directed toward resolving these issues for potential clinical translation of HbV designs as a synthetic RBC substitutes. 31,[96][97][98] Interestingly, instead of encapsulating Hb, some research approaches have also attempted to encapsulate oxygen (O 2 ) directly within phospholipid microvesicles (2-4 μm in diameter) to deliver O 2 to deoxygenated RBCs in circulation. 99,100 Although these oxygen-loaded microbubbles were found to be stable for a few weeks in storage with only small extent of oxygen loss, in vivo they have a very short circulation lifetime (<1 h).…”
Section: Encapsulated Hboc Systemsmentioning
confidence: 99%
“…Further research is currently being directed toward resolving these issues for potential clinical translation of HbV designs as a synthetic RBC substitutes. 31,[96][97][98] Interestingly, instead of encapsulating Hb, some research approaches have also attempted to encapsulate oxygen (O 2 ) directly within phospholipid microvesicles (2-4 μm in diameter) to deliver O 2 to deoxygenated RBCs in circulation. 99,100 Although these oxygen-loaded microbubbles were found to be stable for a few weeks in storage with only small extent of oxygen loss, in vivo they have a very short circulation lifetime (<1 h).…”
Section: Encapsulated Hboc Systemsmentioning
confidence: 99%
“…More specific therapeutic proteins have been encapsulated in liposomal formulations to improve release at a specific site. Basic fibroblast growth factor (bFGF), nerve growth factor (NGF), hemoglobin (Hb) are some of the biomolecules examined (Xie et al, 2005;Xiang et al, 2011;Yadav et al, 2016). It was observed that by using either a pH gradient method or freeze-thawing followed by extrusion, similar bFGF encapsulation yield (∼80%) were obtained (Xiang et al, 2011).…”
Section: Methods For Preparing Liposomesmentioning
confidence: 99%
“…PEGylated (stealth) liposomal formulations have been studied for protein delivery, for instance as safe and effective means to deliver protein antigens (tetanus toxoid (TT), ovalbumin) to potent antigen-presenting dendritic cells for the induction of CD4+ and CD8+ T-cell response in vivo (Ignatius et al, 2000). Hemoglobin (LEH)-loaded liposomes, prepared with anionic lipid hexadecylcarbamoylmethyl-hexadecanoate (HDAS), cholesterol and HDAS-conjugated PEG2000, were tested as oxygen nanocarriers, and succeed in preventing systemic inflammation and multi-organ injuries caused by hemorrhagic shock in mice (Yadav et al, 2016).…”
Section: Liposome Composition For Protein Deliverymentioning
confidence: 99%
“…For HbV preparation, l,2-dioctadecadienoyl-sn-glycero-3-phosphatidylcholine (DODPC) was used as the major membrane phospholipid, such that γ-irradiation-induced radiolysis of water molecules in the vesicles generated hydroxy (–OH) radicals that promoted intermolecular polymerization of dienoyl groups to produce highly stable liposomes that could withstand freeze-thawing, freeze-drying, and rehydration processes. The HbV design has resulted in substantial improvement of circulation life-time (~60 h in some animal models) and several refinements of this design have been reported in recent years (112116). The oxygen transport ability of HbVs was found to be similar to natural RBCs, with comparable oxygen saturation and release kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown significant promise of HbVs as RBC-inspired oxygen carrier; however, these systems can still present issues of broad size distribution of the vehicles, variations in Hb-encapsulation efficiencies, variable pharmacokinetics, and complement-mediated immune response in vivo . Further research is currently being directed toward resolving these issues for potential clinical translation of HbV designs as well as other analogous designs of liposome-encapsulated hemoglobin (LEH) systems RBC surrogates (112116). Interestingly, instead of encapsulating Hb, some recent research approaches have also attempted to encapsulate oxygen (O 2 ) directly within phospholipid microvesicles (2–4 μm in diameter) to deliver O 2 to deoxygenated RBCs in circulation (117, 118).…”
Section: Introductionmentioning
confidence: 99%